An Analysis of Verbal Humor Found in Sitcom Tetangga Masa Gitu - Febby Wahyuni; Hamzah Hamzah (English Language and Literature, 2019)
AbstractNowadays, humor is something that has significant role in daily life. Humor can be found in any aspects in human life, such as in education, literature, and also entertainment. One of various entertainment in Indonesian Television that contain humor is situation comedy. This research pay attention in analyzing verbal humor by using theory of Shade (1996) and analyze the types of verbal humor by using General Theory of Verbal Humor (GTVH). The method used in the research is descriptive method. The result of the study shows that there were 81 verbal humor found in sitcom Tetangga Masa Gitu: Pun (1,2%), Joke (2,4%), Satire (32,2%), Anecdote (1,2%), Irony (34,5%), Sarcasm (8,3%), Tall tale (8,3%), and Wit (110,7%). There were no Riddle, Limerick, Parody and Farce in this object. The verbal humor that found in both object was analyzed by using six parameters of Knowledge Resources (KRs) of GTVH. The six parameters are Script Opposition (SO), Logical Mechanism (LM), Situation (SI), Target (Ta), Narrative Strategy (NS), and Language (LA).Key words: Verbal Humor, Types, GTVH, Six Knowledge Resources